2017
DOI: 10.3390/ijerph14040359
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Types of Ambient PM2.5 and Under-Five and Maternal Mortality in Africa

Abstract: Exploring the effects of different types of PM2.5 is necessary to reduce associated deaths, especially in low- and middle-income countries (LMICs). Hence we determined types of ambient PM2.5 before exploring their effects on under-five and maternal mortality in Africa. The spectral derivate of aerosol optical depth (AOD) from Moderate Resolution Imaging Spectroradiometer (MODIS) products from 2000 to 2015 were employed to determine the aerosol types before using Generalized Linear and Additive Mixed-Effect mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 27 publications
5
37
2
1
Order By: Relevance
“…While there are many studies examining the conditions, interventions and policies that correlate with child-health outcomes in Africa, most are applied at subnational scales or focus on single regions or nations,13–15 and most examine one or only a few hypothesised variables at a time2 5 8 13 16–18 (online supplementary information, table S1). Indeed, a recent study mapping child growth in Africa between 2000 and 2015 identified subnational trends in stunting, wasting and underweight prevalence, but did not directly test any plausible correlates potentially driving the spatial and temporal trends 2.…”
Section: Introductionmentioning
confidence: 99%
“…While there are many studies examining the conditions, interventions and policies that correlate with child-health outcomes in Africa, most are applied at subnational scales or focus on single regions or nations,13–15 and most examine one or only a few hypothesised variables at a time2 5 8 13 16–18 (online supplementary information, table S1). Indeed, a recent study mapping child growth in Africa between 2000 and 2015 identified subnational trends in stunting, wasting and underweight prevalence, but did not directly test any plausible correlates potentially driving the spatial and temporal trends 2.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic emissions of air pollutants have been increasing in the last few years, leading to poor air quality in the region (IMF, 2017;Norman et al, 2007). Fine particulate matter (PM 2.5 with equivalent aerodynamic diameters ≤ 2.5 µm) is one of the major concerns of international organizations and the public because of its high health impacts related to personal exposure (Bruce et al, 2000;Chen et al, 2013;Owili et al, 2017). Owili et al (2017) found that four types of ambient PM 2.5 , including mineral dust, anthropogenic pollutants, biomass burning and mixed aerosols are significantly associated with under-five and maternal mortality in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Fine particulate matter (PM 2.5 with equivalent aerodynamic diameters ≤ 2.5 µm) is one of the major concerns of international organizations and the public because of its high health impacts related to personal exposure (Bruce et al, 2000;Chen et al, 2013;Owili et al, 2017). Owili et al (2017) found that four types of ambient PM 2.5 , including mineral dust, anthropogenic pollutants, biomass burning and mixed aerosols are significantly associated with under-five and maternal mortality in Africa. However, studies on PM 2.5 , especially tests of direct personal exposure to fine particulate matter (hereafter defined as PE PM 2.5 ) (nonstationary sampling) and its health assessment, are very limited in these low gross domestic product (GDP) countries.…”
Section: Introductionmentioning
confidence: 99%
“…The southern West Africa (SWA) region has experienced an economic upturn and increasingly significant anthropogenic air pollutant emissions during the last few years and causes serious air pollution (IMF, 2017;Norman et al, 2007). Fine particulate matter (PM2.5 with equivalent aerodynamic diameters ≤ 2.5 μm) is one of the major concerns of international organizations and publics because of the health effects associated with exposure levels, health of individuals and pollutant emission sources (Bruce et al, 2000;Chen et al, 2013;Owili et al, 2017). Owili et al (2017) found that the four types of ambient PM2.5, including mineral dust, anthropogenic pollutant, biomass burning and mixture aerosols are significantly associated with under-five and maternal mortality in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Fine particulate matter (PM2.5 with equivalent aerodynamic diameters ≤ 2.5 μm) is one of the major concerns of international organizations and publics because of the health effects associated with exposure levels, health of individuals and pollutant emission sources (Bruce et al, 2000;Chen et al, 2013;Owili et al, 2017). Owili et al (2017) found that the four types of ambient PM2.5, including mineral dust, anthropogenic pollutant, biomass burning and mixture aerosols are significantly associated with under-five and maternal mortality in Africa. However, studies on PM2.5, especially direct personal exposure to PM2.5 (not stationary sampling) and its health effects are still limited in low income countries in this region.…”
Section: Introductionmentioning
confidence: 99%